Adult Asian osteomalacia. Issue 674 (December 1981) - Melikian, V.
Abstract : Twenty-four patients from the Indian sub-continent with osteomalacia were treated with calciferol 1·25 mg daily for periods of up to 8 years. Despite the large dose of calciferol, no vitamin D toxicity (hypercalcaemia) occurred.